A multivariate comparative clinical pharmacotherapeutic efficacy and chronopharmacovigilance assessment study of ofloxacin, one of the commonplace, TGFβ1 inducing and telomerase impairing fluoroquinolones, in treating acute gastroenteritis, chronic obstructive pulmonary disease, new drug-sensitive tuberculosis, recurrent mixed cutaneous infections, and post-surgical refractory wound infections, among the global patients, with heterogenous pharmacogeographic and pharmacogenomic constitution - Hazra, Moumita (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Ofloxacin has an inhibitory effect on DNA gyrase, DNA topoisomerase IV and IL-1α, IL-6, IL-8, TNFa; and a superinducing effect on IL-2. Ofloxacin has profound bactericidal, anti-tubercular, anti-leprotic, anti-viral including anti-coronavirus, anti-fungal, anti-protozoal, comedolytic, anti-comedogenic, anti-inflammatory, immunomodulatory, and anti-malignant: pro-apoptotic and anti-proliferative potential, including TGFb1 targeted G2 phase cell cycle arrest and telomerase activity impairment. Objectives of the study were a comparative clinical pharmacotherapeutic efficacy and chronopharmacovigilance assessment study, of ofloxacin, one of the commonplace TGFb1 inducing and telomerase impairing fluoroquinolones, in treating heterogenous global patients, suffering from different diseases. Methods: A prospective, multivariate study of 100 patients, allotted into group A (acute gastroenteritis) =20, group B (chronic obstructive pulmonary disease) =20, group C (new drug-sensitive tuberculosis) =20, group D (recurrent mixed cutaneous infections) =20, and group E (post-surgical refractory wound infections) =20, was prescribed ofloxacin 200-400 mg twice daily, according to required prescribed regimens. A comparative pharmacotherapeutic efficacy assessment was made from the complete recovery time-periods, including the residual recovery time-periods. The chronopharmacovigilance assessment was made by adverse effects occurrence monitoring during treatment period or follow-up, with an Adverse Event Case Report Form. Results: The residual recovery time-periods, in group A=0 days, group B=2 days, group E=3 days, group D=3 days, and group C=7 days. Adverse effects were not statistically significant, with a predictable chronopharmacovigilance illustration. Conclusions: The pharmacotherapeutic efficacy of ofloxacin was more for treating group A, followed by group B, followed by group E and group D, and finally followed by group C. Ofloxacin was safe, without any pharmacogenomic or pharmacogeographic heterogeneity related fluctuation.